Management of atrial fibrillation in seven European countries after the publication of the 2010 ESC Guidelines on atrial fibrillation: primary results of the PREvention oF thromboemolic events—European Registry in Atrial Fibrillation (PREFER in AF). Issue 1 (1st October 2013) - Kirchhof, Paulus; Ammentorp, Bettina; Darius, Harald; De Caterina, Raffaele; Le Heuzey, Jean-Yves; Schilling, Richard John; Schmitt, Josef; Zamorano, Jose Luis
Abstract: Aims: We sought to describe the management of patients with atrial fibrillation (AF) in Europe after the release of the 2010 AF Guidelines of the European Society of Cardiology. Methods and results: The PREFER in AF registry enrolled consecutive patients with AF from January 2012 to January 2013 in 461 centres in seven European countries. Seven thousand two hundred and forty-three evaluable patients were enrolled, aged 71.5 ± 11 years, 60.1% male, CHA2 DS2 VASc score 3.4 ± 1.8 (mean ± standard deviation). Thirty per cent patients had paroxysmal, 24.0% had persistent, 7.2% had long-standing persistent, and 38.8% had permanent AF. Oral anticoagulation was used in the majority of patients: 4799 patients (66.3%) received a vitamin K antagonist (VKA) as mono-therapy, 720 patients a combination of VKA and antiplatelet agents (9.9%), 442 patients (6.1%) a new oral anticoagulant drugs (NOAC). Antiplatelet agents alone were given to 808 patients (11.2%), no antithrombotic therapy to 474 patients (6.5%). Of 7034 evaluable patients, 5530 (78.6%) patients were adequately rate controlled (mean heart rate 60–100 bpm). Half of the patients (50.7%) received rhythm control therapy by electrical cardioversion (18.1%), pharmacological cardioversion (19.5%), antiarrhythmic drugs (amiodarone 24.1%, flecainide or propafenone 13.5%, sotalol 5.5%, dronedarone 4.0%), and catheter ablation (5.0%). Conclusion: The management of AF patients in 2012 has adapted to recent evidence and guideline recommendations. Oral anticoagulant therapy with VKA (majority) or NOACs is given to over 80% of eligible patients, including those at risk for bleeding. Rate is often adequately controlled, and rhythm control therapy is widely used.